2012
DOI: 10.5120/6194-8715
|View full text |Cite
|
Sign up to set email alerts
|

Malware Detection using Windows API Sequence and Machine Learning

Abstract: Monitoring the behavior of program execution at run-time is widely used to differentiate benign and malicious processes executing in the host computer. Most of the existing run-time malware detection methods use the information available in Windows Application Programming Interface (API) calls. The proposed malware detection system uses the Windows API call sequence. A 3rd order Markov chain (i.e. 4-grams) is used to model the API calls. This composite feature set is provided as an input to the malware detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 6 publications
0
38
0
Order By: Relevance
“…Do antivirus programs apply against worms and Trojans or only against the viruses? All of these questions originate from one source and it's the complex and complicated world of destructive codes [1].…”
Section: Malware Definition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Do antivirus programs apply against worms and Trojans or only against the viruses? All of these questions originate from one source and it's the complex and complicated world of destructive codes [1].…”
Section: Malware Definition and Analysismentioning
confidence: 99%
“…Like country boundaries which could be attacked from different aspects such as contraband and thieves, virtual space also suffer from these attacks [1]. Experiences have shown that most of these attacks are from malwares.…”
Section: Introductionmentioning
confidence: 99%
“…Ravi, et al [3] proposed a malware detection system which used Windows API call sequence as an input and association mining based classification. To create a signature database, the proposed system split a sequence into 4-gram and labeled them with their corresponding class according to the rules.…”
Section: Related Workmentioning
confidence: 99%
“…Generally dynamic analysis has two ways according to the used feature and applied technique. Firstly, dynamic analysis by the used features utilizes information such as the frequency or sequence of API call [1], [3]- [5], compiled hexadecimal code [2], program execution paths [8] and others [5]- [7] as the feature. Secondly, analysis by applied techniques utilizes a sequence alignment [1], [2] and data mining or machine learning [2]- [5], [9] for the collected feature data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation